Caribbean college receives study materials - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Students of the Barbados Community College Associate Degree in Agriculture programme now have access to a wealth of new reading and research material. This is the result of a recent presentation of 108 books, fact sheets and technical bulletins by...